Addressing the Urban Heat Island Effect in Yogyakarta: The Role of Human Behaviour and Community Engagement in Mitigating Heat Impacts - Kiswantoro, Amin; Hendratono, Tonny; Supina, Supina; Susanto, Dwiyono Rudi; Sugiarto, Sugiarto (Universitas Pendidikan Ganesha, 2024)
Environmental researchers have extensively examined the effects of urban heat islands. However, there seems to be a dearth of research on how communities perceive and engage with these effects. Urban heat effects have been a major environmental concern in Yogyakarta for the last 11 years. Urban heat islands have been widely studied, but research on community perceptions of these effects is limited. Therefore, this study investigates the impact of awareness and knowledge, personal experience, and perceptions on communities' involvement in addressing urban heat island effects, given the significant impact of humans and their potential role as generators of these issues. This study used partial least squares structural equation modeling using SmartPLS version 4.1.0.3 to look at the proposed measurement and structural models based on 481 onsite-collected responses. Findings showed that, although knowledge and awareness do alter how communities feel about being involved in the environmental care activities, they do not have much of an impact on how active the communities actually are. On the other hand, personal experience and perceptions have a significant impact on the effectiveness of community involvement, although they do not alter perceptions of participation. This study highlights the importance of developing targeted strategies that consider both the perceptions and practicalities of community engagement. In managing urban heat islands, it is essential to combine behavioral insights with effective solutions, such as reflective roofing and urban green initiatives. Future research should include longitudinal studies and explore additional factors such as social support and motivational drivers.